Healthcare professionals’ knowledge, attitudes, and practice of podoconiosis management and associated factors in public hospitals in Ilu Ababor and Buno Bedelle zones, Southwest Ethiopia: a cross-sectional study - Tamiru, Sanbato; Lulu, Yohanis; Bidira, Kebebe; Amsalu, Bonsa; Duguma, Abdissa; Nigusu, Yared; Gezimu, Wubishet (Frontiers in Public Health, 2025)
BackgroundPodoconiosis is non-filarial lymphoedema of the lower extremities. It impairs individuals’ overall lives, including their health, economy, psychology, and social interactions. Podoconiosis is a preventable and effectively manageable disease. The insights and skills of healthcare professionals are vital for the prevention and management of podoconiosis. However, healthcare professionals’ knowledge, attitudes, and practices of podoconiosis management have been poorly studied in Ethiopia.ObjectiveThe study aimed to assess the healthcare professionals’ knowledge, attitudes, and practices toward podoconiosis management and associated factors in public hospitals in the Ilu Ababor and Buno Bedelle Zones.MethodsA facility-based cross-sectional study was conducted from December 1, 2022, to January 1, 2023. The data were collected from systematically selected health professionals using a self-administered structured questionnaire. Epi-data and SPSS were used for data entry and analysis, respectively. A binary logistic regression analysis was used to identify factors influencing the outcome variables. In the multivariable analysis, a p-value of ≤0.05 was used to pronounce statistical significance at a 95% confidence interval.ResultsFrom the total of 399 participants involved, 262 (65.7%) had poor knowledge, 213 (54.3%) had unfavorable attitudes, and 308 (77.2%) had never practiced podoconiosis management. Years of experience, level of education, type of qualification, podoconiosis training, taking courses in education curricula, and attitudes were identified as factors influencing knowledge. The participants’ attitudes were influenced by age, podoconiosis training, receiving technical support, and knowledge. Their practices were significantly affected by age, education level, podoconiosis training, taking podoconiosis courses in educational curricula, and knowledge.ConclusionThe current study found poor healthcare professionals’ insights and skills in podoconiosis management in the study area. Therefore, concerned bodies need to set up capacity-building training and guidelines for healthcare professionals in the area to boost their knowledge, attitudes, and practice toward podoconiosis management.